HUBUNGAN ANTARA PENGGUNAAN MEDIA SOSIAL DENGAN KESEPIAN DAN PERILAKU PERBANDINGAN SOSIAL - Sri Wahyuning Astuti; Yenny Yenny (Jurnal Psikohumanika, 2021)
The development of social media is increasingly massive, forcing more and more interactions from its users. So far, studies on the influence of the use of social media only refer to one particular social media. This study aims to look at the intensity of social media use with loneliness and social comparisons. The sample in this study were social media users using random sampling with the help of google form. The intensity of social media use is measured using the Intensity scale of Social Media Use which has dimensions of attention, appreciation, duration and frequency, while to measure using the UCLA-3 scale, and social comparison is measured using the IOWA, the results show a positive relationship between intensity of social media use. with loneliness and social comparisons. Thus, the higher the intensity of the use of social media, the more it will cause loneliness and make social comparisons to its users.